Effect of Amaranth and Quinoa Flours on Exopolysaccharide Production and Protein Profile of Liquid Sourdough Fermented by Weissella cibaria and Lactobacillus plantarum - Valerio, Francesca; Bavaro, Anna Rita; Di Biase, Mariaelena; Lonigro, Stella Lisa; Logrieco, Antonio Francesco; Lavermicocca, Paola (Frontiers in Microbiology, 2020)
Exopolysaccharides (EPS) are known for their positive contribute to the technological properties of many foods, including bakery products. These molecules can be obtained performing piloted fermentation with lactic acid bacteria (LAB). In order to select strains able to produce EPS, a screening test in agar medium containing sucrose, fructose or glucose as carbohydrate source was performed on 21 LAB strains. Results allowed to select 8 Weissella cibaria, 2 Weissella confusa and 2 Leuconostoc spp. strains as EPS producers only in the presence of sucrose. A further screening in liquid medium enriched with sucrose (10%) (mMRS_S) indicated the W. cibaria strain C43-11 as the higher EPS producer. The selected strain was used to develop liquid sourdoughs (LSs) with dough yield (DY) 500, fermented for 15 h and based on wheat flour and wheat gluten or pseudocereals (quinoa or amaranth) in ratio 1:1, in the presence or not of sucrose at 3% (w/w, LS weight), in comparison to Lactobacillus plantarum ITM21B, a strain not producing EPS in mMRS_S. Results indicated that the use of pseudocereals favored the EPS production. Formulations were optimized by modifying DY (500 or 250), sucrose concentration (3 or 6%) and flour ratio. LSs were characterized for the content of organic acids (lactic, acetic, phenyllactic, OH-phenyllactic), pH, TTA, EPS, viscosity, total protein degradation and protein pattern. The highest EPS production (20.79 g/Kg) and viscosity (1168 mPa s) were obtained in LS (DY 250, sucrose 6%) based on quinoa flour and started with C43-11 strain. The LS was characterized by the presence of phenyllactic and OH-phenyllactic acids, protein degradation by 51.7% and proteins in the range 14-80 kDa. In these conditions, also strain ITM21B was able to produce EPS at level of 4.61 g/Kg and to degrade proteins by 53.8% in LS based on wheat and quinoa flours (1:1) (DY250 and sucrose 3%). Therefore, results demonstrated that the use of selected conditions (flour type, DY, sucrose) can stimulate specific attributes of strains making them suitable for production of short fermented (15h) liquid sourdoughs which can be used as bread improvers.